Presurgical Psychological Screening : Understanding Patients, Improving Outcomes - Block, Andrew; Sarwer, David B. (American Psychological Association, 2013)
"The success of many surgical procedures depends not only on the skill of the surgeon and the use of state-of-the-art technology, but also on the actions and characteristics of the patient. Patients' emotional and psychosocial concerns, health-related behaviors, outcome expectations, and compliance with treatment regimen can all strongly influence the ultimate effectiveness of surgery. Thus, mental health professionals are increasingly called upon to perform presurgical psychological screening (PPS) to ensure that patients are given the treatments most likely to be effective, while reducing the chances of worsening their conditions. Each chapter in this book examines psychosocial influences on surgery for a specific medical condition. In general, the earlier chapters represent those areas in which PPS is already in common use: organ transplantation, spinal surgery, bariatric surgery, and pain control procedures. Conditions in which PPS is being used with increasing frequency represent the next group of chapters: stem cell and bone marrow implantation, deep-brain stimulation for Parkinson's disease, surgery for temporomandibular joint disorder, reconstructive surgery, breast surgery, and gynecologic surgery. The final chapters examine conditions for which PPS is beginning to be used but has not come into wide acceptance: carpal tunnel syndrome and cosmetic surgery. Drawing on both research and clinical experience, the authors explain how to conduct PPS, communicate results to patients and surgeons, and identify possible pre- or postsurgery interventions to mitigate risk factors and maximize the likelihood of surgical success. Case studies and a discussion of bioethics are included. The Afterword suggests future directions for the field."--(PsycINFO Database Record (c) 2012 APA, all rights reserved).